Screening of Microbial Natural Products and Biological Evaluation of Trichomicin as Potential Anti-Cytokine Storm Agents - Chen, Yu; Zhuang, Zhuochen; Yang, Jing; Bai, Liping (Frontiers in Pharmacology, 2021)
COVID-19 has remained an uncontained, worldwide pandemic. Most of the infected people had mild symptoms in the early stage, and suddenly worsened or even died in the later stage which made the cytokine release syndrome (CRS) once again aroused people's attention. CRS is an excessive immunity of the body to external stimuli such as viruses, bacteria, and nanomaterials, which can cause tissue damage, local necrosis or even death. Lipopolysaccharide (LPS) is one of the most effective CRS inducers, which can activate macrophages to release cytokines, including tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), IL- 6 and chemokines. We used RT-PCR to detect the expression of representative cytokines in mouse and human cells at different concentrations of Trichomicin, Ebosin and 1487B after LPS stimulation. The results showed that the expression of TNF-α, IL-1β, IL-6 and CXCL10 all increased after LPS stimulation. Among the various drugs, Trichomicin had the most obvious inhibitory effect on cytokine expression in vitro, and it was further verified in vivo that Trichomicin can improve the survival rate of mice stimulated with LPS. Finally, it was proved that Trichomicin inhibited the Stat3 and NF-κB pathways and reduced the phosphorylation of Stat3 and p65 after LPS stimulation, thereby inhibiting the response of macrophages to pro-inflammatory stimuli. The article clarified the inhibitory activity and mechanism of action of Trichomicin on CRS, and laid the foundation for the research on the anti-cytokine storm activity of microbial natural products.